Learning Situations for Inclusion of Environmental Topics in Chemistry Classes in Costa Rican Secondary School (Biocenosis, 2022)
The study consisted in the elaboration and evaluation of an Environmental Chemistry Workshop (ECW) aimed at students and professors of the career of Natural Science Teaching at Distance State University, Costa Rica (UNED-CR). The objective was to approach a series of learning situations (LS) regarding the inclusion of environmental topics in the Diversified Education Chemistry Program of the Ministry of Public Education (MEP). The workshop was called The Chemistry of the Environment: A Strategy for Inclusion in the Secondary School Curriculum. The LS included activities such as: case studies, home experiments, use of simulators and research projects. The workshop was held asynchronously with Microsoft Teams®; it lasted two weeks and had a population of 39 participants. Finally, an evaluation was applied using a survey (Office Forms 365®). It was determined that the workshop provided teachers with materials, teaching tools, and current learning situations that were attractive to students and helped them promote scientific skills in the classroom.
Keywords: workshop; chemistry; environment; education; learning situations